An analysis of the resistance of an extended end-plate beam-to-beam connection subjected to tension in fire conditions - Słowikowska, Alina; Polus, Łukasz (Budownictwo i Architektura / Civil and Architectural Engineering, 2019)
This paper presents an analysis of the fire resistance of a steel joint subject-ed to tension. The authors of this article used prescriptive rules and simple calculation models to present an impact of the value of the load on the fire resistance of the connection. Designers often evaluate the critical temperature and fire resistance time of steel elements. However, they neglect the evaluation of the above-mentioned values for steel connections. In this article a simple engineering method was used to calculate the fire resistance of the joint.